Postcolonial or Not? : West Africa in the Pre-Atlantic and Atlantic Worlds - Christopher R. DeCorse (IFRA-Nigeria, 2013)
What do the labels "Historic period," "historical archaeology," and "Colonial" imply about the source materials drawn on, the time periods covered, and the conceptual vantages taken in interpreting the West African past? The historiographies presented are equally relevant to the understanding of the past-that is, the impacts of European contact, the Atlantic slave trade, and colo- nization-as they are to the present; the social, economic, and cultural landscapes of modernity, and how our views of the past shape these landscapes. This essay considers the varied epistemological threads represented and their interpretive implications. Although the hegemonic and transformative nature of Africa's intersection with the Atlantic World is underscored, the need to situate these developments within the wider scope and temporal depth of the African past is also emphasized. Archaeology's central role in providing a holistic understanding of the temporal depth and complexity of African history, as well as archaeology's unique contribution to the understanding of the Atlantic world, is underscored.